Unique Variant Complex Chromosome Translocation in Myeloid Leukemia: Report of a Case and Literature Review - Abolfazl Movafagh (Middle East Journal of Cancer, 2012)
Background: According to the literature, there are a number of chronic and acute myeloid leukemias with unique, complex chromosome translocations. This study aims to conduct a brief review of the incidence of complex chromosome translocations in myeloid leukemia and reports a case of myeloid leukemia with complex chromosome translocations.Methods: We conducted a web-based search for all peer review articles published on the subject of complex chromosome tranlsocations in chronic and acute myeloid leukemia in MEDLINE, PubMed and Mitelman (http://cgapanci.nih.gov/chromosomes/Mitelman) databases in addition to other pertinent web references. In addition, we performed conventional cytogenetic studies of 24- to 72-h cultures on bonemarrow/peripheral blood cells obtained from the current case. Cells were finally treated by the giemsa-trypsin-giemsa banding technique.Results: The result of this case revealed an abnormal karyotype that had a novel complex translocation which involved chromosomes 2, 5, 9, and 22. We performed karyotyping after the initiation of chemotherapy. Karyotyping results showed a complex karyotype 46,XX,t(9;22;2;5).Conclusion: This study discusses a case of chronic myeloid leukemia with complex chromosome translocations and may provide novel information regarding these translocations in leukemias.